Structural relaxation in pure liquids: Analysis of wavenumber dependence within the approach of generalized collective modes - Bryk, T.; Mryglod, I. (Condensed Matter Physics, 2008)
Wavenumber dependence of structural relaxation in liquids is studied by the method of generalized collective
modes (GCM). A new perturbation approach within the GCM method is proposed and applied in the longwavelenth
limit in order to obtain analytical expressions for the wavenumber-dependent structural relaxation
and sound dispersion within a simplified three-variable dynamical model. Analytical results are compared with
numerical study of generalized modes within a more general five-variable dynamical model, which accounts
for thermal processes in liquids. Numerical results are presented for four thermodynamic points of Lennard-
Jones fluid at the reduced temperature T* = 1.71. We discuss the features of non-hydrodynamic process of
structural relaxation in different regions of wavenumbers. Залежнiсть вiд хвильового числа для структурної релаксацiї в рiдинах дослiджується методом узагальнених колективних мод (УКМ). Запропоновано новий пертурбативний пiдхiд в рамках методу УКМ, що застосовано для знаходження залежної вiд хвильового числа структурної релаксацiї та дисперсiї звуку у довгохвильовiй границi в рамках спрощеної тризмiнної динамiчної моделi. Аналiтичнi результати порiвнюються iз числовими дослiдженнями узагальнених мод в рамках бiльш загальної п’ятизмiнної динамiчної моделi, що враховує термiчнi процеси в рiдинах. Представлено числовi результати для чотирьох термодинамiчних точок ленард-джонсiвського плину з приведеною температурою T* = 1.71. Обговорюються особливостi негiдродинамiчного процесу структурної релаксацiї у рiзних областях хвильових чисел.